Molecular Viscosity Sensors with Two Rotators for Optimizing the Fluorescence Intensity–Contrast Trade-Off - Lee, Seung Chul; Lee, Chang Lyoul; Heo, Jeongyun; Jeong, Chan Uk; Lee, Gyeong Hui; Kim, Sehoon; Yoon, Woojin; Yun, Hoseop; Park, Sung O.; Kwak, Sang Kyu; Park, Sung Ha; Kwon, O. Pil (Chemistry - A European Journal, 2018)
A series of fluorescent molecular rotors obtained by introducing two rotational groups (“rotators”), which exhibit different rotational and electron-donating abilities, are discussed. Whereas the control molecular rotor, PH, includes a single rotator (the widely used phenyl group), the PO molecular rotors consist of two rotators (a phenyl group and an alkoxy group), which exhibit simultaneous strongly electron-donating and easy rotational abilities. Compared with the control rotor PH, PO molecular rotors exhibited one order of magnitude higher quantum yield (fluorescence intensity) and simultaneously exhibited significantly higher fluorescence contrast. These properties are directly related to the strong electron-donating ability and low energy barrier of rotation of the alkoxy group, as confirmed by dynamic fluorescence experiments and quantum chemical calculations. The PO molecular rotors exhibited two fluorescence relaxation pathways, whereas the PH molecular rotor exhibited a single fluorescence relaxation pathway. Cellular fluorescence imaging with PO molecular rotors for mapping cellular viscosity was successfully demonstrated.
Keywords: Cellular fluorescence imaging; Dyes/pigments; Electron-donating; Electron-donating ability; Fluorescence intensities; Molecular rotors; Molecular viscosity; Quantum chemical calculations; dyes/pigments; fluorescence; molecular rotors; sensors; viscosity